Living Hadis Nilai-nilai Inti Sistem Manajemen Strategis pada Pengelolaan Pendidikan Tinggi - Rahmah, Siti; Darmalaksana, Wahyudin; Vera, Susanti; Firdaus, Muhamad Yoga (Jurnal Riset Agama, 2021)
This study aims to discuss the core values in strategic management systems. This research method is qualitative through literature study with a living hadith approach which is a case study in Islamic higher education. The results and discussion of this research are in the form of a vision, mission, goals, strategic objectives, and core values of Islamic higher education institutions. These are substantially understood as a manifestation of the management of the Prophet, as a noble person with al-Qur'an morals. This study concludes that the relevant living hadith approach is used for research on the core values of strategic management systems that are initiated by institutions in their efforts to achieve strategic goals. The recommendation of this research is the importance of developing hadith studies and developing value-based institutions as a reference for decision making.